Character Education Model in Wayang Kulit for Early Childhood - Junaidi, Junaidi; Raharjo, Arif Budi; Sahid, Nur; Sukanadi, I Made; Wicaksana, Dewa Ketut; Purnamasari, Ni Putu Laras (Harmonia: Journal of Arts Research and Education, 2024)
This study explains the character education model in wayang kulit art for early childhood (5 to 6 years old) as one support to form their future personality. This study is based on an action research approach to improve character quality to be better than before. The subjects are male or female students following and understanding character education through wayang kulit. The action method transforms adult puppet into children, concludes figures with positive character, and is responsible for early childhood to be actively involved in education and wayang kulit. The results show that positive character education, such as diligence, sincerity, firmness, helpful, determination, wiseness, humility, fairness, and friendliness, is found in human and animal children characters named Punta, Sena, Juna, Pinten, Tangsen, Bledug, and Belo which follows the child's developmental level rapidly advancing towards the future, and it can be used in the early childhood and kindergarten education environment nationally and internationally. Thus, much support is needed from children's educational institutions and wayang kulit arts, i.e., Kemdikbudristek (Ministry of Education, Culture, Research, and Technology of Indonesia), Kemen KPP-PA (Ministry of Women Empowerment and Children Protection of Indonesia), SENAWANGI (National Secretariat of wayang kulit of Indonesia), PEPADI (Association of Indonesian Wayang Kulit), UNIMA, UNICEF, and UNESCO, to achieve a culture-based character education program.